The Role of Institutional Investors in Capital Market Development: A case study of Mutual Funds in Ghana - Dadzie-Wilson, Lordina Ewuradwoa (2021)
Over the years, Institutional Investors, particularly Mutual Funds, have played a critical role in the development of Capital Markets in developed, emerging, and developing markets. Existing empirical evidence on this subject is rather mixed, and in developing markets like Ghana, this is limited. Thus, this study evaluated the role of Institutional Investors in the development of Ghana's Capital Market, with a particular emphasis on Mutual Funds. The application of trend analysis over a ten-year period (2010–2019) revealed that Institutional Investors are a key contributor to capital accumulation and allocation to stock market capitalisation, despite great room for future expansion. An assessment of the Institutional environment found the existence of a framework that supports Institutional Investors' corporate governance role. The Granger causality test applied to monthly data from January 2012 to December 2020 indicated the existence of a unidirectional causal relationship running from stock market performance to equity Mutual Fund stock market allocation. Thus, the results suggest that in Ghana, Mutual Fund investments in the stock market are determined by the performance of the stock market. Based on the findings, the regulator and government should work closely together to reduce market volatility and maintain stability. Domestic Institutional Investors should be encouraged to participate more actively in the stock market in order to act as stabilisers against foreign investors' portfolio reversals. Following the lead of the United Kingdom and Malaysia, a stewardship code and network of Institutional Investors should be established to improve the corporate governance of publicly traded firms, resulting in improved performance, higher stock prices, and market returns.